MAKNA HEALING DI KALANGAN MAHASISWA DI UNIVERSITAS NEGERI MAKASSAR - Muhammad Ibnu Hannan; Sopian Tamrin; Muhammad Aksha Wahda (Yayasan Literasi Sains Indonesia, 2026)
This study aims to determine the forms of healing activities undertaken by students and analyze how they interpret healing as part of social dynamics. The study used a qualitative approach with a phenomenological method to understand students' subjective experiences. Informants were selected using purposive sampling from the Faculty of Mathematics and Natural Sciences, Faculty of Language and Literature, Faculty of Engineering, Faculty of Sport and Health Sciences, Faculty of Education, Faculty of Social Sciences and Law, and Faculty of Psychology. Data were collected through observation, in-depth interviews, and documentation. Data validity was checked using triangulation techniques. Data analysis techniques were carried out through data reduction, data presentation, and drawing conclusions. The results showed that healing activities include simple activities such as playing games, watching digital content, reading books, cleaning rooms, to outdoor activities such as walks to the beach, mountains, parks, or nature tours with friends. Healing is defined as an activity carried out in leisure time to strengthen social relations and build self-image on social media. Thus, healing among students is a phenomenon that functions as a representation of lifestyle and social identity in contemporary digital culture. Healing cannot be separated from the social context, digital culture, and academic structures surrounding students. From a leisure perspective, healing can be understood as not only an act of coping with stress, but also a social practice imbued with symbolic meaning.